Role of ethnicity in high-level obstetric clinical incidents: a review of cases from a large UK NHS maternity unit. Issue 4 (15th November 2022) - Farrant, Kimberley; Faluyi, David; Watson, Kylie; Vause, Sarah; Birds, Heather; Rowbotham, Shirley; Heazell, Alexander EP
Abstract : Introduction: Women from ethnic minority groups are at more risk of adverse outcomes in pregnancy compared with those from white British groups; suboptimal care may contribute to this increased risk. This study aimed to examine serious clinical incidents at two maternity units to explore causative factors for women from ethnic minorities and determine whether these differed from white women. Methods: A retrospective review was conducted of all serious incidents (n=36) occurring in a large National Health Service maternity provider ( 14 000 births per annum) between 2018 and 2020. Data were collected from case records for variables which could mediate the association between ethnicity and adverse outcome. The incident reviews were blinded and reviewed by two independent investigators and data regarding root causes and contributory factors were extracted. Results: Fourteen of the 36 incidents (39%) occurred in women from minority ethnic groups, which is comparable to the maternity population. Women involved in serious clinical incidents frequently had pre-existing medical or obstetric complications. Booking after 12 weeks' gestation occurred more frequently in women from minority ethnic groups than in the background population. There were differences in root causes of serious incidents between groups, a lack of situational awareness was the most frequent cause in white women and staff workload was most frequent in women from minority ethnic groups. Communication issues and detection of deterioration were similar between the two groups. Discussion: Although there was no difference in the proportion of serious incidents between the groups, there were differences in medical and pregnancy-related risk factors between groups and in the root causes identified. Efforts are needed to ensure equity of early access to antenatal care and to ensure that there is adequate staffing to ensure that women's needs are met; this is particularly cogent when there are complex medical or social needs.